2020
DOI: 10.25115/ecp.v13i27.3659
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level in students regarding age, gender, sport and motivational climate | Nivel de actividad física en estudiantes en función de la edad, el género, tipo de deporte practicado y su orientación motivacional

Abstract: ResumenEl objetivo del trabajo es conocer el nivel de actividad física y la orientación motivacional en función del género, la edad y el tipo de deporte practicado en estudiantes. La muestra estuvo compuesta por 285 estudiantes (150 chicos y 135 chicas), con edades comprendidas entre los 11 y 18 años (edad media = 14.85 ± 3.42), a los que se les administraron los cuestionarios Physician-based Assessment and Counseling for Exercise y Goal Orientation in Exercise Scale. Los resultados mostraron que, el nivel de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
2
0
2
Order By: Relevance
“…On the other hand, higher values were observed in the variables that make up the ego climate for males, coinciding with another research already carried out [31]. Tese diferences according to gender have been explained by diferent authors, who consider social factors that infuence the forms of sports socialisation [32]. Likewise, females tend to conceive sport as an activity of a cooperative nature, oriented towards leisure and enjoyment, while for males, the competitive factor of sport predominates [33].…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, higher values were observed in the variables that make up the ego climate for males, coinciding with another research already carried out [31]. Tese diferences according to gender have been explained by diferent authors, who consider social factors that infuence the forms of sports socialisation [32]. Likewise, females tend to conceive sport as an activity of a cooperative nature, oriented towards leisure and enjoyment, while for males, the competitive factor of sport predominates [33].…”
Section: Discussionsupporting
confidence: 81%
“…10(1), 2022 www.physactiv.eu _____________________________________________________________________________________ 136 60 minutes of daily PA at 1300-15000 steps for school-age boys and 11000-12000 steps for their girl peers, is taken as a reference for discussing the results. In Spain, Parra and his colleagues [22] suggest a generic threshold of 10000 steps for adolescents (11000 for boys and 10500 for girls), although it should be taken into account the significant drop in PA levels in the transition between Primary and Secondary Education [27,28]. In any case, the average of 9000 of the studied group has been the minimum recommended daily PA for these ages, confirming the first of the proposed hypothesis.…”
Section: Recommended Daily Steps and Pa Levelsmentioning
confidence: 67%
“…Focusing on the mediating role of satisfaction with PE, several studies have found that when a student has fun and feels satisfied with PE classes, their intention to be active in their leisure time will increase [10,20,28], with task orientation being a strong predictor of satisfaction with PE [12]. This relationship could be due to the fact that when adolescents are task-oriented, they tend to make an effort in their personal development, focusing their satisfaction on self-improvement [47,50,51], thus increasing their satisfaction with PE [12,48]. Various authors have highlighted the importance of strengthening student satisfaction and motivation in order to continue physical activity outside the school classroom [3,32,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%